Geriatric assessment of older patients with cancer in Australia—A multicentre audit. Issue 3 (May 2015) - Lakhanpal, Roopa; Yoong, Jaclyn; Joshi, Sachin; Yip, Desmond; Mileshkin, Linda; Marx, Gavin M.; Dunlop, Tracey; Hovey, Elizabeth J.; Della Fiorentina, Stephen A.; Venkateswaran, Lakshmi; Tattersall, Martin H.N.; Liew, Sem; et al.
Abstract Objective The aim of this study is to determine the frequency of geriatric assessment in patients aged over 70 years in Australian medical oncology clinics. Material and Methods This was a multicentre audit in two parts: a retrospective file review of initial consultations with an oncologist and prospective audit of case presentations at multidisciplinary meetings (MDMs). Patients aged over 70 years presenting to a medical oncology clinic or being discussed at an MDM were eligible. Data was collected at six oncology centres in Victoria, NSW and Canberra from October 2009 to March 2010. Results Data was collected from 251 file reviews and 108 MDM discussions in a total of 304 patients. Median age was 76 years (range 70–95). The geriatric assessment (GA) domains most frequently assessed during an initial consultation were the presence of comorbidities (92%), social situation—living alone or with someone (80%), social supports (63%), any mention of at least one Activity of Daily Living (ADL) (50%) and performance status (49%). Less frequently assessed were any Instrumental Activity of Daily Living (IADL) (26%), presence of a geriatric syndrome (24%), polypharmacy (29%) and creatinine clearance (11%). Only one patient had all components of ADLs and IADLs assessed. During MDMs all the geriatric domains were comparatively less frequently assessed. No patients had all ADL and IADL components discussed formally in an MDM. Conclusion This is the first multicentre audit that reveals the low rates of GA in Australian medical oncology practice and describes the GA domains considered important by oncology clinicians.